Experimental Study on Performance of Zero-emission Heat Pump System for Exhaust Gas after Drying Process in Pharmaceutical Industry - Yu Yingrui; Wei Juan; Li Weizhao; Zhang Chong; Li Bo; Yang Luwei (Zhileng xuebao, 2023)
This study develops a zero-emission heat pump system consists of heat pipes, water coils, and heat pumps for exhaust gas to mitigate the incomplete treatment, disgusting smell, and unrecoverable heat of exhaust gas after the drying process in the pharmaceutical industry. The quality of gas recycling and reuse is guaranteed by closed-loop dehumidification, waste gas treatment, and heating, thereby achieving near-zero emissions and recovery of waste heat. The experimental results of the system performance show that when the average temperature of the supply air is 65.1 °C, the relative humidity of the supply air is 21.1%, the air volumetric flow rate is 12 000 m3/h, the coefficient of performance of the heat pump unit is 4.7, and the specific moisture extraction rate of the system is 8.5 kg/(kW?h). The composition of the circulating gas shows that 73.2% of the volatile organic compounds are absorbed, and no non-condensable, flammable, or explosive gases are accumulated in the system during each production period.